Finance management and liquidity: An analysis in an electrification company in Lima - Chung-Sanchez, Kenji A. (2024)
The research analyzed the impact of finance management (FM) on the liquidity (L) of a company specializing in the production of electrical panels and the execution of electrification projects in Lima. The study, which was quantitative, applied, and correlational in nature, adopted a non-experimental, longitudinal design. Observation and document recording techniques were used for data collection. All the information was extracted from validated financial statements submitted to the tax administration during the fiscal years 2017 to 2022. The study showed a clear and strong association between finance management and liquidity, evidenced by a Pearson correlation coefficient of 0.812 and a determination coefficient of 0.7. It was concluded that efficient financial management has a significant and positive impact on the company's liquidity. The proper optimization of financial resources allowed the company to maintain the necessary liquidity to cover expenses. This finding is crucial for the company, as good financial management not only ensures a sound cash flow in the short term but also lays the foundation for sustainable long-term growth.